Impact of the operating mode of neutral in 35 kV power grids on the arc overvoltages and voltage teasuring transformers - Yatseyko, Andriy; Andrushko, Volodimir (Lviv Polytechnic Publishing House, 2015)
Has been analyzed possible methods of earthing of neutrals in 35 kV power grid. Among the most common injuries in these electrical system are arc circuits, that is why the dependence of overvoltage multiplicities on the nature of earth arcing and on the method of earth arrangement of electrical system neutral. Given that in 35 kV power grids may arise ferroresonant processes, operation of voltage measuring transformers has been researched during unstable earth arcing.
Keywords: power grid; arc overvoltage; digital model; insulated neutral; resonant-earth neutral; overvoltage ratio; resistance-earth neutral; voltage transformers